Pseusdoscorpiões (Arachnida) da Serapilheira e suas Relações com Fatores do Solo, da Reserva Florestal Adolpho Ducke, Manaus, Amazonas, Brasil - Gualberto, Tomaz Lima (Instituto Nacional de Pesquisas da Amazônia - INPA, 2003)
We investigated the differences in the abundance, richness and distribution of species of edaphic pseudoscorpions in relationship to environmental factors (percentage of clay, content of aluminum, carbon and iron, pH of soil, inclination of the land and litter layer) and the difference between two main drainage basins (East and West) at Adopho Ducke Forest Reserve, Manaus, Amazonas. On a system of trails within 64 km2 , we collected 360 sub-samples of 0,25 m2 of litter, in 72 parcels of 250 m length, performing 72 samples. We recorded 659 individuals belonging to 7 species, 6 genus and 4 families: Chthoniidae Daday, I 888 (Pseudochthonius homodentatus Balzan, 1 892, Tyrannochthonius irmlen Manhert, 1979 e Tyrannochthonius minor Manhert, 1979), Ideoroncidae Chamberlin, 1 930 (Albiorix gracilis Man hert, 1 985), Syarinidae Chambberlin, 1930 (Ideobisium shusferi Manhert, 1 985 e Ideoblothrus tenuis Manhert, I 985) and Atemnidae C hamberlin, 1 931 (Brazilatemnus browni Muchmore, 1 975). Ideobisium shusteri was the most abundant (48%) followed by Brazilatemnus browni (21 %), Albionic gracilis (1 2%) e Pseudochthonius homodentatus (1 0%). Tyrannochthonius irmleri is recorded for the first time in Ducke Reserve. In the regression anaysys, the mean density of Ideobisium shusteri had significant correlation with the percentage of clay, and Tyrannochthonius minor with the amount of litter. The species richness also showed significant correlation with the amount of litter. We hypothesize that these species found at the litter layer can not be use as good biological indicators, as they were equally distributed n the two main drainage basins. For future studies we must take in consideration the evaluation of other habitats Iike mineral soil, trunks and vegetation to investigated the relationship of the species of pseudoscorpions to environmental factors.
Keywords: Pseudoscorpiões; Arachnida